O Juiz das Garantias e o Sistema Acusatório no Processo Penal Brasileiro - Oliveira, Manollo Sedano de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The present work aims to analyze the implementation of the figure of the Judge of Guarantees in Brazil and its consequences, from the perspective of the accusatory procedural system, in force in the country since the Federal Constitution of 1988. Despite criticisms of the figure, the study will seek to demonstrate that the benefits that permeate the institute vastly outweigh any problems. Thus, we will seek to briefly highlight the judge of guarantees in Portuguese and Chilean legislation, in addition to the empirical experience developed by Professor Schünemann based on studies by Leon Festinger and Martin Irle, demonstrating how the "cognitive dissonance theory" affects human beings and thus, to prove the indispensability of the institute's insertion in the national legal system, as a way to increasingly seek an impartial judge, in order to implement a democratic and constitutional criminal process. The method used is bibliographic and the approach is systemic, dialectical, deductive and comparative. After the analysis, it is necessary to conclude that the Judge of Guarantees, like what already happens in other countries in Latin America and Europe, is an important advance in the realization of the judge's impartiality and in the search for a judgment without "prejudices" and with respect to fundamental guarantees and rights.

O presente trabalho tem como escopo analisar a implementação da figura do Juiz das Garantias no Brasil e as suas consequências, sob a ótica do sistema processual acusatório, vigente no país desde a Constituição Federal de 1988. Em que pese haverem críticas à figura, o estudo buscará demonstrar que os benefícios que permeiam o instituto superam enormemente quaisquer problemas. Desse modo, buscaremos evidenciar brevemente o juiz das garantias nas legislações portuguesa e chilena, além da experiência empírica desenvolvida pelo professor Schünemann com base nos estudos de Leon Festinger e Martin Irle, demonstrando como a “teoria da dissonância cognitiva” afeta os seres humanos e assim, comprovar a imprescindibilidade da inserção do instituto no ordenamento jurídico pátrio, como forma de buscar cada vez mais um julgador imparcial, de forma a concretizar um processo penal democrático e constitucional. O método utilizado é o bibliográfico e o de abordagem é o sistêmico, dialético, dedutivo e comparativo. Após a análise é mister concluir que o Juiz das Garantias, a exemplo do que já acontece em outros países da América Latina e da Europa, é um avanço importante na concretização da imparcialidade do julgador e na busca de um julgamento sem “pré-conceitos” e com respeito às garantias e direitos fundamentais.
Judge of Guarantees and the Acussatory System in Brazilian Criminal Proceedings
Keywords: Judge of guarantees; Theory of cognitive dissonance; Accusatory system; Juiz das garantias; Teoria da dissonância cognitiva; Sistema acusatório